2018
DOI: 10.3389/fpls.2018.00380
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study for Identification and Validation of Novel SNP Markers for Sr6 Stem Rust Resistance Gene in Bread Wheat

Abstract: Stem rust (caused by Puccinia graminis f. sp. tritici Erikss. & E. Henn.), is a major disease in wheat (Triticum aestivium L.). However, in recent years it occurs rarely in Nebraska due to weather and the effective selection and gene pyramiding of resistance genes. To understand the genetic basis of stem rust resistance in Nebraska winter wheat, we applied genome-wide association study (GWAS) on a set of 270 winter wheat genotypes (A-set). Genotyping was carried out using genotyping-by-sequencing and ∼35,000 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 36 publications
1
60
0
Order By: Relevance
“…The only drawback of breeding research is the cost and time consuming to achieve its goals. The recent advances in DNA technology and genomics paved the way to identify genomic regions controlling important traits such as drought tolerance in crops (Sandhu et al 2014;Hussain et al 2017;Eltaher et al 2018;Mourad et al 2018). These technologies provide DNA markers that can be combined with phenotypic data to identify genomic regions associated with target traits using genetic association analyses such as genome-wide association study, QTL mapping, single-marker analysis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The only drawback of breeding research is the cost and time consuming to achieve its goals. The recent advances in DNA technology and genomics paved the way to identify genomic regions controlling important traits such as drought tolerance in crops (Sandhu et al 2014;Hussain et al 2017;Eltaher et al 2018;Mourad et al 2018). These technologies provide DNA markers that can be combined with phenotypic data to identify genomic regions associated with target traits using genetic association analyses such as genome-wide association study, QTL mapping, single-marker analysis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…GWAS is a powerful approach that identi es novel alleles associated with complex traits by utilizing linkage disequilibrium and examine marker-trait associations [17][18][19]. It has been applied successfully to study the genetic architecture of disease resistance in different crops such as rice [20], maize [21], grain sorghum [22], and wheat [23][24][25][26]. Maccaferri et al, (2015) reported association mapping of the resistance to the American race of P. striiformis using a world-wide collection of spring wheat genotyped by DArT markers.…”
Section: Introductionmentioning
confidence: 99%
“…SSR markers are characterized with high polymorphisms, good repeatability, co-dominance, and distribution throughout whole genome, and favored for QTL mapping and molecular breeding in wheat [8][9][10]. With rapid advancements in sequencing technology, high-throughput sequencing or chipbased SNP genotyping platforms have been used for QTL mapping [11][12][13][14]. Additionally, the wheat reference genome was assembled and released recently [15].…”
Section: Introductionmentioning
confidence: 99%